Pengaruh Model Pembelajaran Problem Based Learning terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Pendidikan Pancasila di SMP PGRI 1 Ciputat - Lestari, Dina; Rustandi, Roni (Jurnal Tinta, 2025)
This study aims to determine the effect of the Problem Based Learning (PBL) model on students' learning outcomes in the subject of Pancasila Education at SMP PGRI 1 Ciputat. The research employed a quantitative approach with a quasi-experimental design, involving two classes: an experimental class that applied the PBL model and a control class that used conventional teaching methods. The research instrument consisted of pretest and posttest questions, which were tested for validity and reliability, resulting in a Cronbach’s Alpha value of 0.745. The findings indicated a significant increase in the posttest scores of the experimental class from 52 to 75.84, while the control class improved from 48 to 67.12. The t-test showed a significant difference between the two groups. It can be concluded that the PBL model has a positive effect on improving students’ learning outcomes.